Oxidative organ damage in a rat model of thermal injury: The effect of cyclosporin A - (:unkn) unknown (ELSEVIER SCI LTD, 1997)
Animal models of thermal trauma implicate oxygen radicals as a causative agent in local wound response, development of burn shock and distant organ injury. It has been proposed that the source of reactive oxygen metabolites could be neutrophils sequestered in systemic organs as a result of the systemic inflammatory reaction to a local burn insult. Recent studies have suggested that cyclosporin A (CsA), a potent immunosuppressive drug, may have effects on neutrophils by modulating the rate of their accumulation during acute inflammatory reactions. This study aimed to determine whether CsA has protective effects on organs remote from the thermal injury. The results demonstrate that there is significant neutrophil accumulation in the gastric mucosa, liver and lung tissues during the early phase of a burn injury and that CsA failed to protect these organs. In conclusion, the data of this study suggest that neutrophil accumulation in liver, lung and gastric mucosa following burn injury may be involved in the pathogenesis of remote organ damage. The results also indicate that CsA failed to reduce the severity of damage in these organs, probably due to its own toxic effects. (C) 1997 Elsevier Science Ltd for ISBI.
Keywords: ACUTE LUNG INJURY; LIPID-PEROXIDATION; FREE-RADICALS; SKIN; IMMUNOSUPPRESSION; TRANSPLANTATION; CHOLESTASIS; ACTIVATION; COMPLEMENT; RECIPIENTS